Biotechnology : recent trends and emerging dimensions - Bhargava, Atul; Srivastava, Shilpi (CRC Press, 2018)
Biotechnology is a multidisciplinary field encompassing microbiology, bichemistry, genetics, molecular biology, chemistry, immunology, cell and tissue culture physiology. This book describes the recent developments in these areas. Current research topics such as Quorum sensing, Integrons, Phytomining are discussed, which would serve as an excellent reference work for both academicians and researchers in the field.